Fetomaternal outcome of pregnancy with COVID-19: a prospective study in a COVID dedicated hospital - Nazma Begum; Z. H. M. Nazmul Alam; Saiqa Rehnuma; Salma Akhter; Dilip Kumar Bhowmik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Given physiological changes in immunological, pulmonary, cardiac, and coagulation systems during pregnancy, pregnant women have long been recognized as susceptible demographic during infectious disease pandemics. Learning about pregnancy outcomes, possible issues, and neonatal health issues in babies delivered to COVID-19-infected mothers is crucial. Study aimed to analyze fetomaternal outcome of pregnancy with COVID-19. Methods: This was a prospective longitudinal study done on COVID dedicated to Sylhet Shahid Shamsuddin Ahmed Hospital, from January 2021 to January 2022. A total of 54 pregnant women admitted with confirmed COVID-19 were included in this study as per inclusion criteria. Results: In this study, most patients were in the 26-33 age group (37.03%), followed by 18-25 age group (33.33%) and 24-40 age group (29.62%). 50% were primigravida. SARS COV-2 infection occurred in 51.85% of pregnant women in the 3rd trimester, 35.18% in the 2nd trimester, and 12.96% in the 1st trimester, 53.7% of patients had a mild case, 9.26% had moderate, and 37.04% had severe symptoms. 12.96% of patients needed ventilation, while 5.56% were in ICU without ventilation but on HFNC. Two patients had 1st-trimester abortion, and three had pre-term delivery. There was one IUFD, ongoing pregnancy in five patients, vaginal delivery in nine patients, and cesarean section in 25 patients. Sepsis occurred in 3.7% of patients, and post-partum hemorrhage in 1.85%. Oxygen was needed for 37.04% of patients with severe pneumonia. Out of 54 patients, 88.88% recovered, and 11.11% died in the hospital. The number of healthy babies was 74.07%, while premature babies were 5.56%, and there were two perinatal deaths. Conclusions: This study concluded that pregnant women with COVID-19 infection are at increased risk of adverse pregnancy and birth outcomes however, a low risk of congenital transmission, and the neonatal outcome was good. The availability of ICU in critical conditions is needed for better pregnancy outcomes.